A educação em moçambique durante o regime ditatorial salazarista: projetos políticos e identidades coletivas (1926-1974) - Ivangilda Bispo dos Santos (2021)
The objective of this dissertation is to investigate how the educational actions from different Mozambican institutions were related to collective identities from the local individuals and the then current political projects from said groups. Thus, the emphasis is in institutions such as the Liceu Nacional Salazar (Salazar National Licee), Escola de Habilitação de Professores Indígenas “José Cabral” (“José Cabral” Indigenous Teaching School), Centro Associativo dos Negros de Moçambique (Mozambique Black’s Association Center), Escola Chinesa (Chinese School), Instituto Moçambicano (Mozambican Institute), Missão Anglicana (Anglican Mission), Missão Suíça (Swiss Mission) and the Episcopalian Methodist Church. In Mozambique the development of literacy and schooling was attached to the process of Portuguese colonization and other diverse social dynamics, such as the presence of protestant mission societies, islamic and asian groups and individuals. In this context, the Catholic Church assumed a major role in schooling, which led to the diffusion of portuguese nationalism, expansion of the catholic faith and the transformation of the cultural practices of a significant part of the african population. It was in opposition of the colonial regime and in defense of Mozambican nationalism that the Frente de Libertação de Moçambique (FRELIMO) emerged in 1962 and elected education as one of its major instruments for the revolutionary transformation of society. The temporal frame for this research are the years from 1962 to 1974, encompassing from the reformulation of colonial politics, the installment of Salazar's dictatorship, the emergence of the anticolonial and independentist movements, the expansion of the educational system to the end of the colonial rule. The research was made from bibliographical studies about the history of education in Mozambique and primary sources such as Portuguese colonial legislation, photographs, newspaper clippings and memorial narratives. In these documents, the discourse articulated by the individuals linked to schooling institutions were analyzed. The aim was to problematize religious, nationalist, racial and/or ethnic identities and beliefs that were present in their proposal of educational initiatives. The theoretical framework for this dissertation is the approach of Connected Histories.And, for the analyses of sources the following concepts were key: colonialism, transnationalism, identity, gender, schooling, discourse, race, and racism. Among the concluding arguments of this work is important to emphasize that the schooling education was a maker of inequalities, an instrument for the influence of westernized gender roles, means for the perpetuation of violence, mainly in the work dynamics. The schooling institutions were also a tool for the instauration of nationalist and religious identities that shaped ethinic/racial relations, consolidating the colonial political project but also made possible for some individuals to have professional mobility.The objective of this dissertation is to investigate how the educational actions from different Mozambican institutions were related to collective identities from the local individuals and the then current political projects from said groups. Thus, the emphasis is in institutions such as the Liceu Nacional Salazar (Salazar National Licee), Escola de Habilitação de Professores Indígenas “José Cabral” (“José Cabral” Indigenous Teaching School), Centro Associativo dos Negros de Moçambique (Mozambique Black’s Association Center), Escola Chinesa (Chinese School), Instituto Moçambicano (Mozambican Institute), Missão Anglicana (Anglican Mission), Missão Suíça (Swiss Mission) and the Episcopalian Methodist Church. In Mozambique the development of literacy and schooling was attached to the process of Portuguese colonization and other diverse social dynamics, such as the presence of protestant mission societies, islamic and asian groups and individuals. In this context, the Catholic Church assumed a major role in schooling, which led to the diffusion of portuguese nationalism, expansion of the catholic faith and the transformation of the cultural practices of a significant part of the african population. It was in opposition of the colonial regime and in defense of Mozambican nationalism that the Frente de Libertação de Moçambique (FRELIMO) emerged in 1962 and elected education as one of its major instruments for the revolutionary transformation of society. The temporal frame for this research are the years from 1962 to 1974, encompassing from the reformulation of colonial politics, the installment of Salazar's dictatorship, the emergence of the anticolonial and independentist movements, the expansion of the educational system to the end of the colonial rule. The research was made from bibliographical studies about the history of education in Mozambique and primary sources such as Portuguese colonial legislation, photographs, newspaper clippings and memorial narratives. In these documents, the discourse articulated by the individuals linked to schooling institutions were analyzed. The aim was to problematize religious, nationalist, racial and/or ethnic identities and beliefs that were present in their proposal of educational initiatives. The theoretical framework for this dissertation is the approach of Connected Histories.And, for the analyses of sources the following concepts were key: colonialism, transnationalism, identity, gender, schooling, discourse, race, and racism. Among the concluding arguments of this work is important to emphasize that the schooling education was a maker of inequalities, an instrument for the influence of westernized gender roles, means for the perpetuation of violence, mainly in the work dynamics. The schooling institutions were also a tool for the instauration of nationalist and religious identities that shaped ethinic/racial relations, consolidating the colonial political project but also made possible for some individuals to have professional mobility.